2021
DOI: 10.9734/jpri/2021/v33i52a33581
|View full text |Cite
|
Sign up to set email alerts
|

Application of Modified Lowa Model Evidence Based Practice on Trauma Care Nurses Regarding Head Injury

Abstract: Background: Head injuries are a regular occurrence in emergency departments around the world, with more than 2 million annual visits in North American EDs and more than 400 000 in the United Kingdom alone. Despite the fact that the mechanism of injury is consistent,, Head injuries are a regular occurrence in emergency departments around the world, with over 2 million visits in North American EDs and over 400 000 in the European Union alone. Regardless of how consistent the injury mechanism is. Objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It is crucial to aware the community about the early signs and symptoms of chronic kidney disease. (13)(14)(15)(16)(17)(18)(19)(20)(21) A scientific study was done in 2018 regarding the relation between chronic kidney disease and cognitive functions and found out that vascular injury can be a major cause of it. The deposition of calcium in the blood vessels makes the blood vessels stiff calcification appears.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to aware the community about the early signs and symptoms of chronic kidney disease. (13)(14)(15)(16)(17)(18)(19)(20)(21) A scientific study was done in 2018 regarding the relation between chronic kidney disease and cognitive functions and found out that vascular injury can be a major cause of it. The deposition of calcium in the blood vessels makes the blood vessels stiff calcification appears.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acyanotic and cyanotic high-flow lesions, as well as those with pulmonary stenosis, should be treated by doctors with a high index of suspicion for the development of pulmonary tuberculosis. (22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Rana Olguntürk, F.Sedef Tunaoğlu, Levent Gökgöz, Leyla Memiş, and Serdar Kula et al reported after seeing clinical improvement, the patient had surgery. The tricuspid valve underwent ringplasty, and the atrial septal defect was repaired.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery and trauma stress responses entail a variety of physiological responses. A significant effect is the stimulation of the renin-angiotensin-aldosterone pathway, which causes altered fluid balance, increased sodium and fluid retention, and decreased urine output [ 5 ]. Additionally, the activated inflammatory response causes vasodilatation and enhanced capillary wall permeability.…”
Section: Reviewmentioning
confidence: 99%
“…Falls and car accidents are the two main factors that cause traumatic brain injuries globally [ 4 ]. Head injuries are common in emergency departments worldwide, with over two million visits in North America and 400,000 in Europe [ 5 ]. A serious public health issue and the primary cause of mortality and disability is traumatic brain injury.…”
Section: Introductionmentioning
confidence: 99%